Assessing the efficacy of isotopic provenancing of human remains in Colombia. (September 2019) - Eck, Christopher J.; DiGangi, Elizabeth A.; Bethard, Jonathan D.
Highlights: Multi-isotopic approaches can enhance skeletal remains provenancing in Colombia. Environmental hetereogeneity creates challenges for Colombian isotopic provenancing. Oxygen and strontium isotope values are reported primarily for the department of Antioquia. Abstract: We report isotopic ratios for δ 18 O and 87 Sr/ 86 Sr from 71 individual human permanent teeth, obtained from 61 individuals with known regions of origins from eight of the 32 departments in Colombia. This survey of the applicability of isotopic provenancing is a vital addition to the ongoing identification efforts within Colombia concerning unidentified decedents recovered from clandestine and cemetery burials. At this time, only median isotopic values are reported due to heterogeneity of inter- and intra-departmental variance among the obtained isotopic values. The use of department of origin as a regional assignment schema is inadequate to effectively georeference unidentified human remains, given the wide-ranging topography and climatic diversity within Colombia. Therefore, a critical need for additional isotopic sampling of individual reference material exists, in order to improve the accuracy of potential region of origin estimates of unknown decedents originating from forensic contexts within Colombia.